HARMONI AGAMA DAN BUDAYA BANGSA INDONESIA (PENERAPAN NILAI – NILAI KEHARMONISAN AGAMA DAN BUDAYA DI KOTA PONTIANAK) - Wahyudi, Edy; Al-Qadrie, Syarif Ali (UIN Sumatera Utara Medan, 2024)
Harmony of Religion and Culture are two very interesting things to be analyzed and studied in more depth. Religion and culture are two things that are well related to each other in Indonesia. Pontianak City is one of the cities that is very thick with its Religious and Cultural Harmony. Therefore, the author takes Pontianak City as the object of research on Religious and Cultural Harmony that the author does in several community areas in Pontianak City.This article is about the Religious and Cultural Harmony of the Indonesian Nation in the City of Pontianak with an emphasis on the discussion on the Application of Religious and Cultural Harmony Values in the City of Pontianak. This research was conducted by the authors in Pontianak City for approximately one week, namely on July 20-27 2023. This research used a descriptive-qualitative research method in which the authors conducted field observations, interviews, and documentation accompanied by searching for literature that supports this research.The results obtained by the authors state that Religion and Culture are not two different or contradictory things. The advantage of this article compared to other articles lies in the discussion between the application of Islamic religious values which are harmonized with the existing culture in social life in a society. At this time, articles that discuss harmony between Islamic religious values and a culture of society are very rare, so this is also an advantage of this article compared to other articles.The author hopes that this article will be of benefit especially for personal writers and readers in general. Not only that, the authors also hope that this article can change the mindset and perspective of people who think that Religion and Culture are two things that are contradictory to each other. Basically Religion and Culture are two things that are interrelated and cannot be separated.